Formulasi dan Evaluasi Sifat Fisik Sediaan Krim Pelembab Wajah (Moisturizer) dari Ekstrak Etanol Daun Ginseng Jawa (Talinum paniculatum gaertn) - Siti Nur Farida; Ani Agustina; Nur Mahdi (Universitas Borneo Lestari, 2022)
Cosmetics are widely circulated in the community, there are many dosage forms, one of which is cream preparations. This preparation is used on the skin, among others, to protect the skin or as a skin softener. Cream preparations that are important in considering a preparation are its physical stability, physical stability, for example, no clumping, no creaming, and no color change. This study aims to determine the results of the formulation and evaluation of physical properties in cream preparations from extracts of Javanese ginseng (Talinum Paniculatum Gaertn) leaves.This research method is experimental. The concentration of Javanese ginseng leaf extract (Talinum Paniculatum Gaertn) was divided into 4 concentrations of F0 (0%), F1 (0.018115%), F2 (0.03623 %) and F3 (0.054345 %) which were formulated into cream preparations. Evaluation of physical properties included organoleptic tests, homogeneity, pH, dispersion and viscosity. The test rasults of oil palm leaf extract showed no significant difference in the pH, dispersion and viscosity tests. Based on the evaluation of the physical properties of the cream, it shows that all formulations have good characteristics.